Upaya Mengembangkan Sikap Modernitas Mahasiswa STAIS/ITSNU Pasuruan Tanpa Meninggalkan Nilai-nilai Islam Ciri Khas an-Nahdliyah - Abdulloh Shodiq (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2023)
The presence of STAIS/ITSNU Pasuruan is an Islamic higher education institution as a post-Aliyah/non-Aliyah madrasa institution inside and outside the Islamic boarding school environment. This higher education institution will produce students who have modern values ​​without having to abandon the characteristics of an-Nahdliyah, where in general students are educated and trained to live simply, be humble, honest, adaptable, not arrogant, respect people. on the other hand, being steadfast in facing all challenges and temptations, being able to live on one's own strength does not require being a civil servant, and being sincere in all deeds, which is in accordance with the characteristics of an-Nahdliyah. However, their orientation remains towards the future, and has modern values ​​that should be implemented.